2020
DOI: 10.1177/0748233720937196
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic adaptability in liver and gastrocnemius muscle of mice following subacute lead toxicity

Abstract: Lead (Pb) is one of several environmental pollutants that adversely affect human health by producing toxicity at the tissue level. The aim of the study was to understand the effects of Pb on the metabolic profiles of liver and gastrocnemius muscle of mice in relation to carbohydrate and fat metabolisms. Swiss albino mice were chosen and divided into two groups, control and Pb-treated. The Pb-treated animals were exposed to Pb at a dose of 5 mg/kg body weight for 30 days orally, which resulted in hypoglycemia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The differences may be due to the different blood Pb levels of the participants in these studies and the non-linear relationship of Pb with TG. In animal experiments, similar conclusions were given (37,38). Mouse exposed to Pb (5 mg/kg body weight) for 30 days orally caused higher TC, LDL-C, HDL-C, and lower TG (37).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The differences may be due to the different blood Pb levels of the participants in these studies and the non-linear relationship of Pb with TG. In animal experiments, similar conclusions were given (37,38). Mouse exposed to Pb (5 mg/kg body weight) for 30 days orally caused higher TC, LDL-C, HDL-C, and lower TG (37).…”
Section: Discussionsupporting
confidence: 53%
“…In animal experiments, similar conclusions were given (37,38). Mouse exposed to Pb (5 mg/kg body weight) for 30 days orally caused higher TC, LDL-C, HDL-C, and lower TG (37). The inverse U-shaped association of Pb with TG was also observed in the Wistar rats (38).…”
Section: Discussionmentioning
confidence: 53%
“…[51][52][53] We did not measure Pb levels in the blood, which is a limitation of our work. A study by Das et al 54 found that Pb had a direct inhibitory effect on hepatic gluconeogenic genes glucose-6 phosphatase expression. Therefore, we speculate that the decreased HOMA-IR in ND mice by Pb exposure may be related to the inhibition of gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We did not measure Pb levels in the blood, which is a limitation of our work. A study by Das et al 54 . found that Pb had a direct inhibitory effect on hepatic gluconeogenic genes glucose‐6 phosphatase expression.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments indicate that the toxic effects of Pb on muscles primarily manifest in disrupting normal glucose metabolism processes, altering the activity of key enzymes, and adjusting energy metabolism, which may also damage muscle tissue structure. These physiological changes could negatively impact muscle function and quality, thereby adversely affecting overall health (Das et al, 2020). In another animal study, it was found that Pb exposure's harm to skeletal muscle function mainly includes reduced muscle mass, decreased exercise capacity, weakened muscle strength, disrupted lipid metabolism, increased inflammatory responses, and upregulated expression of pro-apoptotic genes.…”
Section: Introductionmentioning
confidence: 99%